Usefullness of Phytoestrogens in Treatment of Arterial Hypertension. Systematic Review and Meta-Analysis: Un Update - Garcia Garcia MA; Rosero Arenas MA; Martinez Cornejo A; Perez Lluna L (Archives of Clinical Hypertension - Peertechz Publications, 2016)
Background: It has been suggested that phytoestrogens may have utility in the control of arterial hypertension. Methods: We performed a systematic review and meta-analysis of randomized controlled trials, and the main outcome was the decrease of blood pressure. Results: Decrease in systolic (- 0,15 mmHg, CI 95% from -0,24 to -0,05) and diastolic (-0,14 mmHg, CI 95% from -0,25 to -0,03) blood pressure were observed in patients taking phytoestrogens, but this difference was not clinically relevant. There can be a little greater decrease in Asian patients and in patients with higher baseline blood pressure values. Conclusion: The global effect of phytoestrogens seems of small amount in reducing blood pressure. Nevertheless, it has not been realized a clinical trials about the efficacy of these products in no mild hypertensive patients, similar to real life.